Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00423-013-1063-8
|View full text |Cite
|
Sign up to set email alerts
|

Early analgesic treatment regimens for patients with acute abdominal pain: a nationwide survey among general surgeons

Abstract: Discordance in the analgesic treatment regimens in patients with acute abdominal pain still exists in German hospitals. The topic remains subject of frequent discussions. More high quality data are needed before a clear guideline can be given for implementation in clinical routine management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There is ongoing controversy about whether pain should be relieved in patients with undiagnosed AAP. [13,14] Some clinicians adhere to the surgical dictum: analgesia should be withheld from patients with AAP, as it may hinder a correct diagnosis. [14] At present, whether to treat the treatment of patients with unknown abdominal pain depends mainly on the doctor's habits and experience.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing controversy about whether pain should be relieved in patients with undiagnosed AAP. [13,14] Some clinicians adhere to the surgical dictum: analgesia should be withheld from patients with AAP, as it may hinder a correct diagnosis. [14] At present, whether to treat the treatment of patients with unknown abdominal pain depends mainly on the doctor's habits and experience.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In a number of previous surveys of emergency physicians 23,28 and surgeons 19 , a large proportion of respondents chose not to provide analgesia until after surgical consultation. This practice has long impeded timely administration of analgesia 34 or led to analgesia being withheld altogether.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, untreated pain in childhood has been reported to lead to long-term negative outcomes such as anxiety, hyperesthesia, and needle phobia. 18 Notwithstanding the above, few EDs have policies guiding pain management in patients with acute abdominal pain, 1,19 and a 2012 study reported that analgesia is not provided to one-third of children with abdominal pain. 20 It is thus imperative to explore reasons behind withholding analgesia, and, more speficially, the relationship of the practice of withholding analgesia with surgical consultation, in order to inform knowledge translation initiatives to improve care.…”
Section: Introductionmentioning
confidence: 99%
“…Analgesia in the setting of undifferentiated abdominal pain has long been an area for controversy; the idea is that "covering the physical findings" will worsen outcomes [8,214]. Fortunately, there are sufficient data refuting this idea-an idea based upon historical cautions formulated due to problems with large opioid doses in the preradiology era-that the question has been answered to a reasonable degree of certainty [179,[215][216][217][218][219][220][221][222][223][224][225][226]. A variety of opioids (including the atypical agent tramadol) have been assessed, as administered a variety of ways ranging from IV bolus [227] to nebulized opioid [228] to patient-controlled analgesia [179], but the bottom line is that existing evidence does not support a practice of having patients suffer to preserve the physical examination [8].…”
Section: Special Issues Withmentioning
confidence: 99%